(untitled) (Research, Society and Development, 2022)
In this work Pd nanoparticles immobilized on a hybrid solid support comprised of Fe3O4 coated by a ZnO layer were synthesized by a green method which makes use of water, a biological substrate from a local plant (Rhamnidium elaeocarpum) and inexpensive Fe3+ and Zn2+ salts. 1H-NMR and 13C-NM revealed β-sitosterol as the main component of the biological substrate. The catalytic support containing Pd nanoparticles was applied in three model solid-liquid catalytic systems, namely: alcohol oxidation, nitrocompound reduction and olefin hydrogenation. For the alcohol oxidation, benzyl alcohol was used as the substrate in a solvent-free condition with high selectivity towards benzaldehyde, and a single sample of the catalyst could be recycled up to 11 times before any loss of activity could be detected. TOF (turnover frequency) as high as 13,686 h-1 for the substrate oxidation was achieved with an average yield rate of 45.4% for formation of benzaldehyde and 81.6% of average substrate conversion after 6 catalytic cycles. For the hydrogenation experiments using cyclohexene and 4-nitrophenol as model substrates, conversion as high as 96% to 4-aminophenol and cyclohexane, respectively, was achieved after 30 minutes of reaction. Furthermore, a single sample of the catalyst could be recycled for up to 17 times for the reduction of 4-nitrophenol, and 21 times in the hydrogenation of cyclohexene. Catalytic recycling for all studied reactions was straightforward after due to the superparamagnetic property of the material, and catalyst isolation after each batch could be rapidly carried out using a Nd magnet. These results suggests that a highly active and stable catalytic system based on Pd nanoparticles supported on a multifunctional solid could be fabricated using green and inexpensive biomass under operationally simple synthesis conditions.